Pertumbuhan dan Nilai Gizi Tanaman Rumput Gajah pada Berbagai Interval Pemotongan - Adrianton Adrianton (Universitas Tadulako, 2010)
The research was aimed at analyzing the growth and nutrition value of elephant grass under different cutting interval times. The research was carried out at the experimental garden of BPTP Gowa, Pa Bentengan Village, Bajeng Sub-district, Gowa Regency, South Sulawesi Province from May 2007 to March 2008. The research utilized a random block design, with 4 treatment levels, i.e.: (1) a four-week cutting interval, (2) a six-week cutting interval, (3) an eight-week cutting interval, (4) a ten-week cutting interval. Each treatment was repeated 3 times, so that 12 treatment units were obtained. The research results showed that the four-week cutting interval produced the best growth and production components such as increased plant height (cm day-1), leaf number (leaf day-1), poll number (poll day-1), wet and dried weight (ton ha-1year-1) The analysis of nutrition value indicated that the 4 week-cutting interval yielded higher water level and crude protein, but lower crude fat and fiber.